Penerapan Familiar Auditory Sensory Training (FAST) terhadap Tingkat Kesadaran Pada Pasien Stroke di Rumah Sakit Jakarta - Firdaus, Nuzula; Jumaiyah, Wati; Yunitri, Ninik; Agung, Rizky Nugraha (Universitas Malahayati, 2024)
ABSTRACT Decreased consciousness in stroke patients can be caused by brain hypoxia due to blockage of blood vessels in ischemic strokes, while in hemorrhagic strokes, bleeding occurs in the brain accompanied by cerebral edema, increasing intracranial pressure (ICP) and causing narrowing of blood vessels and herniation of brain tissue. FAST sensory stimulation carried out by the family is more effective in influencing the patient's level of consciousness compared to stimulation carried out by nurses. FAST intervention, compared to other sensory stimulation, is a non-invasive method, with low risk, affordable cost, and simple in application, making it an attractive intervention and can be easily applied in patients with decreased consciousness. Data analysis in this paper applies univariate data analysis to observe demographic characteristics and changes in the level of awareness of each respondent. Next, statistical tests were used with the paired t-test to evaluate the effect of awareness level before and after implementing Familiar Auditory Sensory Training, with a significance level of 0.05. The author counted the number of respondents using G*Power Version 3.1 software (Kang, 2021) with a total of 11 respondents. Data analysis in this paper applies univariate data analysis to observe demographic characteristics and changes in the level of awareness of each respondent. Next, statistical tests were used with the paired t-test to evaluate the effect of awareness level before and after implementing Familiar Auditory Sensory Training, with a significance level of 0.05. The author counted the number of respondents using G*Power Version 3.1 software (Kang, 2021) with a total of 11 respondents. The characteristics of participants in the implementation of EBNP show that the majority are men (76.9%) with a high school education level (46.2%), Javanese ethnicity dominates (46.2%), and self-employed work dominates (53.8%). Participants' ages varied, with a mean of 53.1 years and a range of 42–67 years. The FAST intervention had a significant impact on patients' level of consciousness, with a mean increase from 10.1 to 11.6. These results show high statistical significance, and the implementation of FAST forms a standard operating procedure that can be adopted at PON hospitals. Keywords: Familiar Auditory Sensory Training (Fast), Level of Consciousness, Stroke Patients. ABSTRAK Penurunan kesadaran pada pasien stroke dapat disebabkan oleh kondisi hipoksia otak akibat sumbatan pembuluh darah pada stroke iskemik, sedangkan pada stroke hemoragik, terjadi perdarahan di dalam otak yang disertai edema serebri, meningkatkan tekanan intrakranial (TIK) dan menyebabkan penyempitan pembuluh darah serta herniasi jaringan otak. Stimulasi sensori FAST yang dilakukan oleh keluarga lebih efektif dalam mempengaruhi tingkat kesadaran pasien dibandingkan dengan stimulasi yang dilakukan oleh perawat. Intervensi FAST, dibandingkan dengan stimulasi sensorik lainnya, merupakan metode non-invasif, dengan risiko rendah, biaya terjangkau, serta sederhana dalam aplikasinya, menjadikannya sebagai intervensi yang menarik dan dapat diterapkan dengan mudah pada pasien dengan penurunan kesadaran. Penerapan Praktik Keperawatan Berbasis Bukti (EBNP) digunakan untuk memahami dampak penerapan FAST terhadap tingkat kesadaran pasien stroke. Analisis data dalam penulisan ini menerapkan analisis data univariat untuk mengamati karakteristik demografi dan perubahan tingkat kesadaran pada setiap responden. Selanjutnya, uji statistik digunakan dengan uji paired t-test untuk mengevaluasi pengaruh tingkat kesadaran sebelum dan setelah penerapan Familiar Auditory Sensory Training, dengan tingkat signifikansi 0,05. Penulis menghitung jumlah responden menggunakan perangkat lunak G*Power Versi 3.1 (Kang, 2021) dengan total 11 responden. Karakteristik peserta dalam implementasi EBNP menunjukkan mayoritas adalah laki-laki (76,9%) dengan tingkat pendidikan SMA (46,2%), suku Jawa mendominasi (46,2%), dan pekerjaan wiraswasta mendominasi (53,8%). Usia peserta bervariasi, dengan rata-rata 53,1 tahun dan rentang 42-67 tahun. Intervensi FAST memberikan dampak signifikan pada tingkat kesadaran pasien, dengan peningkatan rata-rata dari 10,1 menjadi 11,6. Hasil ini menunjukkan signifikansi statistik yang tinggi, dan penerapan FAST membentuk standar operasional prosedur yang dapat diadopsi di RUMAH SAKIT JAKARTA . Kata Kunci: Familiar Auditory Sensory Training (Fast), Tingkat Kesadaran, Pasien Stroke